The meaning of dwelling. Insights from the classical thought - Chiodo, Simona (Scenari, 2021)
The classical thought (making reference to etymology, myth and philosophy) may promisingly help us reason on the meaning of dwelling. In particular, if we try to consider the notion of dwelling together with the notion of architecture, then we get to the following result, which seems quite interesting also in order to reason on the present: starting from the notion of architecture, and in particular from the meaning of arché, which is the remarkably philosophical word that founds it (together with tektonia), implies an idea of precedence that seems alternative to Heidegger’s notion of dwelling as the cause, and not the effect, of building. This possible shift, which enriches the ways in which we may reason on both architecture and dwelling, may give us possible suggestions that are still meaningful.